2004
DOI: 10.1175/bams-85-11-1745
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Monsoon Rainfall and River Discharge on 15–30-Day Time Scales

Abstract: A new physically based prediction scheme for 20-30-day variability shows promise in monsoon regions for agricultural planning, disaster mitigation, and flood forecasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
158
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 176 publications
(162 citation statements)
references
References 57 publications
4
158
0
Order By: Relevance
“…Thus, intraseasonal variability, possibly a phenomenon independent of ENSO, may dilute the overall impact of ENSO on the predictability of the monsoon. Intraseasonal variability strongly influences regional rainfall and is a source of extended range predictability of monsoon weather (Lawrence and Webster 2001;Webster and Hoyos 2004;Wang et al 2005a, Hoyos andWebster 2007). Therefore, it is important to assess the prediction skill of the monsoon intraseasonal variability in state-of-the-art ocean-atmosphere coupled forecasting system.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, intraseasonal variability, possibly a phenomenon independent of ENSO, may dilute the overall impact of ENSO on the predictability of the monsoon. Intraseasonal variability strongly influences regional rainfall and is a source of extended range predictability of monsoon weather (Lawrence and Webster 2001;Webster and Hoyos 2004;Wang et al 2005a, Hoyos andWebster 2007). Therefore, it is important to assess the prediction skill of the monsoon intraseasonal variability in state-of-the-art ocean-atmosphere coupled forecasting system.…”
Section: Discussionmentioning
confidence: 99%
“…High potential usefulness of intraseasonal forecasts for agriculture, society and economy has triggered a number of research activities to develop empirical as well as dynamical models for extended range prediction of monsoon ISV. During the past few years, several studies (Waliser et al 1999;Mo 2001;Webster and Hoyos 2004;Jones et al 2004) have demonstrated the feasibility of predicting the active-break spells of ISM 20-25 days in advance. These models, however, could not be effectively used for real time operational forecasting due to nature of time filters involved in constructing the empirical models.…”
Section: Introductionmentioning
confidence: 99%
“…With 2/3 of the Indian population depending on agriculture for employment and 2/3 of the cultivated land relying on rainfed farming, water and food security closely follow climate variability and extremes. Thus, seasonal predictions of the onset and strength of monsoon rainfall are crucial for water resources as well as agricultural management and planning in India (Webster and Hoyos, 2004;Siddiq, 1999). During the monsoon season, usually from June to September, the Indian subcontinent receives 80-90% of the total annual rainfall in a sequence of rainy periods (monsoon bursts) and dry periods (monsoon breaks) of 10-20 days duration which stem, although they appear at first sight to be quite random, from intra seasonal oscillations (Webster and Hoyos, 2004).…”
Section: Introductionmentioning
confidence: 99%